Sovereignty, sustainability, and Indigenous community control in Canada: In conversation with Stan Knight - McCartney, Shelagh (Canadian Planning and Policy / Aménagement et politique au Canada)

(untitled) (Association of Canadian University Planning Programs, 2026)
This special issue features an interview with Stan Knight, the developer of Inspector in a Box, a knowledge training tool designed to improve housing quality and inspection capacity in northern and Indigenous communities. Knight’s work reflects the importance of practical innovation and community engagement in addressing the systemic challenges of northern housing. In preparing this piece, Knight met with Shelagh McCartney for a conversation about his experiences with topics ranging from construction standards to local capacity building. By situating technical expertise within broader discussions of sovereignty, sustainability, and community control, his perspective underscores how tools for knowledge transfer can contribute to more just and resilient housing futures in the North.